Avaliação das emissões superficiais do gás de aterros sanitários de grande porte - Silva, Tiago Nascimento; de Freitas, Fernando Souza Nazareth; Candiani, Giovano [UNESP] (FapUNIFESP (SciELO), 2013)
The present work showed the results of the biogas surface emissions from two large landfills. The study methodology consisted on escaping biogas analysis on the landfill surface, through the flux box and laboratory analysis. The total average emission of Bandeirantes Landfill was 0.00126 m3.CH4.m-2.h-1 and in Caieiras Landfill it was of 0.01222 m3.CH4.m-2.h-1. Those results were used to determinate the biogas escape both landfills. The total escape in Bandeirantes Landfill biogas accounted for 16% and in Caieiras, 35%. The conclusions demonstrated that there is a significant loss of biogas through the surface in both landfills, thus compromising the efficiency of the capture for using biogas.
Evaluation of surface emissions of gas from large landfills
Keywords: Biogas; Collection system; Flux box; Landfill; Methane; Surface emission